The Biblical Motif of a Pastoral Journey in “The Garden of Divine Songs” by Hrygorii Skovoroda - Dzhydzhora, Yevgen (Slavistica Vilnensis, 2025)
This article examines a specific local issue in biblical interpretation found in some poems in H. Skovoroda’s poetic collection, “The Garden of Divine Songs”. It focuses on the biblical motif of a pastoral journey, which is revealed through the praise of the preacher’s legs. This motif appears in two biblical texts: The Book of the Prophet Isaiah and The Epistle of Paul to the Romans, where the shepherd’s journey is portrayed, emphasising his ‘beautiful legs’. The tradition of associating travelling evangelists with ‘beautiful legs’ also persists in some medieval Slavic works, which is a course that H. Skovoroda follows. In three dedication songs of his “The Garden of Divine Songs”, the theme of a pastoral journey is evident. Notably, the 25th song highlights the legs of a preacher travelling for the episcopal throne to Belgorod. In the 26th song, the arrival of another Church figure to the episcopal throne in Pereyaslav is celebrated. Lastly, the 27th song describes the ‘beautiful legs’ of another bishop’ in relation to his pastoral visit to Kharkiv Collegium. H. Skovoroda engages with various biblical phrases in these three songs while consistently interpreting the same motif and symbolic characteristic.
Keywords: biblical hermeneutics; biblical symbols; biblical quotes; baroque; motif; spiritual poem